(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the issues of liability for the infringement of know-how rights from both legal-theoretical and practical perspectives. Know-how, as a form of trade secret, is considered an important object of intellectual property that protects the economic interests of enterprises and business entities. Violations of these rights, including unlawful disclosure, unauthorized use, or transfer to third parties, negatively affect not only the rights and interests of the owner but also the overall environment of fair competition. The article analyzes international legal norms, in particular the TRIPS Agreement, as well as the mechanisms of know-how protection in the United States, the European Union, China, and Japan.